Az ipari termelés szerepének és területi szerkezetének változáas Magyarországon napjainkban - Győri, Ferenc; Pál, Ágnes (Közép-Európai Közlemények, 2016)
We want to present the historical back-ground of the changes in the industry of Hungary emphasizing the continousness in terms. The renewing and transforming of the industry of Hungary is a permanent process. After the fall of socialism the interest of the multinational companies and enterprises strenghtened regarding the role of investors. In this transition economy the role of the market has immensely been emphasized, the role of the privatization is a characteristic feature this time. One and a half decades after the regime change Hungary joined the European Union (2004). The economy of Hungary became an open economy. From 2008 the structure of the industry has been changed. The economic crisis caused a lot of structural changes regarding a set of the connections in the economy. Today a re-industrialization process can be observed. The industrial output is increasing, the driving force of the process is the automotive industry. The traditional NE-SW axle presented the previous line of the main territory of the production of the industry. The new territory is the northern part of Transdanubia, instead of the previous area. Hungary’s industry is still in a period of transition. It depends on the effects of globalization, the world’s economic processes, the volume of operating capital, the success of economic restructuring and the possibilities for cooperation between eastern and western economies. All these factors influence Hungarian economy as a whole, since it is closely related to both European and global economies.